Two new species of flukes (Digenea: Bucephalidae: Prosorhynchinae) from the Western Moray Gymnothorax woodwardi (Anguilliformes: Muraenidae) from off Western Australia, with replacement of the pre-occupied generic name Folliculovarium Gu & Shen, 1983 - Nolan, M. J.; Cribb, T. H. (Systematic Parasitology, 2010)
Two new species of bucephalid trematodes are described from the rectum and intestine of the western moray eel Gymnothorax woodwardi McCulloch (Anguilliformes: Muraenidae: Muraeninae) off Point Peron in Western Australia. Dollfustrema gibsoni n. sp. is distinguished by body size, a pharynx that is intertesticular and level (latero-dextrally) with the anterior portion of the cirrus-sac, an ovary positioned dextrally to the testes and slightly anterior to (in part) the anterior testis, a uterus that extends anteriorly to the vitelline follicles but not to the level of the rhynchus, and vitelline follicles that form a confluent arc anterior to the gonads. Muraenicola nom. nov. is proposed as a replacement generic name for the pre-occupied Folliculovarium Gu & Shen 1983 nec Singh & Sinha 1981. Muraenicola botti n. sp. is distinguished from its congeners by body size, the size of the cirrus-sac (relative to body size), and in possessing tegumental spines, testes that are oblique (rather than in tandem) and eight ovarian lobes. It differs further in having an intestinal caecum that extends anteriorly to the level of the vitelline follicles and in the position of the pharynx and cirrus-sac relative to each other (lateral in part) as well as to the gonads. M. botti n. sp. also lacks a metraterm. These are the first reports of these genera from fishes off Australia and from the southern hemisphere.